Manajemen Pelayanan Kesehatan di Pondok Pesantren Attanwir Bojonegoro Jawa Timur - Siti Fatimatul Fajriyah; Fahrurrozi; Baqiyatush Sholihah (STAI Terpadu Yogyakarta, 2021)
In education management, health service management is part of special service management. Disease problems that continue to exist and are often experienced by santri of pesantren, especially attanwir pesantren are scabies (scabies), itching, shortness of breath, fever, fainting, cough, runny nose, mild pain, and ulcers. RSKLSM Attanwir is a health clinic that was established to help improve health and welfare as well as improve the healthy life of pesantren residents. RSLKSM operational activities involve students who are members of Santri Siaga with the vision of